PENERAPAN METODE REDUCE, REAUSE DAN RECYCLE PADA LINGKUP KEPERAWATAN KOMUNITAS DALAM MENGATASI MASALAH KESEHATAN LINGKUNGAN YANG BERFOKUS PADA SAMPAH RUMAH TANGGA DI PROBOLINGGO - NURUL LAILI (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2022)
Unclean environmental conditions and unhealthy behavior are the causes of the problem of the emergence of infectious diseases. One example of poor clean, healthy living behavior is the lack of awareness in disposing of waste in its place and improper ways of managing household waste. Almost all areas are experiencing difficulties obtaining land as a final disposal site. The government cannot solve the problem of household waste alone. Sentong Village does not correctly manage waste; for example, all waste is burned, and there is no separation between organic and inorganic waste. The purpose of this community service is to increase public awareness by increasing general knowledge about proper waste management and empowering the community to manage waste with the Reduce, Reuse, and Recycle method as one of the appropriate methods in processing household waste. The results of community service activities show that the community is quite enthusiastic when given information about proper waste management; the methods used in these activities are the lecture and discussion methods, then pre-test and post-test are carried out; the community who attended the training were 15 people, and residents agreed to apply the right way of processing waste, starting with the correct way of disposing of waste, namely distinguishing between organic and inorganic waste, so as not to litter in front of the house.